Impact of anatomical factors on surgical planning and outcomes in high-risk patients undergoing prophylactic mastectomy - Maciulaitis, Tomas; Gudavicienė, Daiva; Jakutis, Nerijus (Frontiers in Surgery, 2025)
BackgroundNipple-sparing mastectomy (NSM) with immediate implant-based reconstruction is widely accepted and effective prophylactic surgical approach for women with high-risk of hereditary BC. However, anatomical factors—advanced breast ptosis and increased sternal notch-to-nipple (SN-N) distance—can increase technical difficulty and complication risk. Preshaping procedures may optimize anatomy and broaden NSM eligibility. This study evaluates the role of preshaping in facilitating safe NSM with implant-based reconstruction.MethodsWe conducted a retrospective analysis of 84 patients who underwent prophylactic mastectomy at Vilnius University Hospital Santaros Klinikos between 2018 and 2024. All had confirmed pathogenic mutations associated with hereditary BC risk. At the time of analysis, 76 patients had completed mastectomy, while 8 had undergone only the preshaping procedure. Patients were divided into two cohorts: single-stage NSM with direct-to-implant reconstruction, and a two-stage approach involving initial preshaping surgery followed by delayed NSM. Anatomical features, surgical timing, complications were analyzed.ResultsAmong 76 patients, 63.2% underwent single-stage and 36.8% two-stage reconstruction. Two-stage patients had significantly greater SN-N distances (26.4 ± 3.1 cm vs. 21.6 ± 3.2 cm, p < 0.001). The overall complication rate was 7.9%, higher in the single-stage group (10.4%) than the two-stage group (3.6%). In the single-stage cohort, complications correlated with higher ptosis grades (p = 0.0021). Ductal carcinoma in situ was found in one patient from each group.ConclusionsPreshaping surgery effectively optimizes anatomy for NSM, reducing complications in patients with ptosis or extended SN-N distances. The two-stage approach offers safe and favorable outcomes in anatomically challenging cases.